Gratuitous violence and the rational offender model - James Foreman-Peck; Simon Moore (Cardiff University, Cardiff Business School, 2009)
Rational offender models assume that individuals choose whether to offend by weighing the rewards against the chances of apprehension and the penalty if caught. While evidence indicates that rational theory is applicable to acquisitive crimes, the explanatory power for gratuitous non-fatal violent offending has not been evaluated. Lottery-type questions elicited risk attitudes and time preferences from respondents in a street survey. Admitted violent behaviour was predictable on the basis of some of these responses. Consistent with the rational model, less risk averse and more impatient individuals were more liable to violence. Such people were also more likely to be victims of violence. In line with a subjective version of the rational model, respondents with lower estimates of average violence conviction chances and of fines were more prone to be violent.
Keywords: D81; K14; 330; violence; alcohol; risk; intertemporal choice; rational offending; Kriminalität; Risikopräferenz; Entscheidungstheorie; Zeitpräferenz; Kriminalitätsökonomik; Theorie